Impact of usable coefficient of adhesion between tyre and road surface by modern vehicle on its dynamics while driving and braking in the curve - Panáček, Vladimír; Semela, Marek; Adamec, Vladimír; Schüllerová, Barbora (Transport, 2016)
The paper deals in detail with the analysis of driving and braking of the Volvo V40 T5 AWD Cross Country vehicle in the curve with radius 30, 40 and 50 meters laying emphasis on usable coefficient of adhesion values between tyre and road surface in the longitudinal and lateral direction. Individual dynamical driving and braking experiments in the curve were carried out using both modes of the Volvo stability system DSTC. We found out the range of values of coefficient of adhesion in the longitudinal and lateral direction depending on the vehicle speed and curve radius of the road. Experimentally determined values are utilised efficiently for the calculation of limit speed of a modern vehicle in the curve or, for instance, at the forensic reconstruction of a road accident.